Caring Experience of Childbirth Primipara Undergone Emergency Cesarean Section: A Systematic Review - Regina Vidya Trias Novita (Jurnal Ilmu Keperawatan Maternitas, 2019)
Introduction: Childbirth is natural phenomenon. The statement ‘fear of death’ and ‘losing the child’ is manifest childbirth among the primipara (Nakano et al, 2012).  Childbirth among the primipara manifest by ‘fear of death’ and ‘losing the child’. Even the mother was happy met her baby, but negative feelings, such as fear, guilt, or anger could lead their memories of the birth (Ryding, 1998). The problems during childbirth process can be affected  both of the mother’s health and baby in the future. Even birth by EmCS,  women could be helped to have more positive chilbirth experiences (Ayers et al., 2006), by created positive athmosphere in maternity ward. There is need to explore caring experience among of primiparaous undergone EmCS, so health care professional understand how to empowerment mothers in  the emergency situation.Objectives :  To conduct a systemetic review of the literatur to explore caring experience of primipara childbirth with emergency cesarean section, to understand the factors internal contributing of caring and the factors hindering or enhancing by health care professional. Methods: A systematic review was performed to explore experience primipara and identify the strategies which measure health care professional delivered care before, during and after emergency emegergency cesarean section (EmCS). The search strategy included database ProQuest and grey literature using Google scholar. Caring experience of childbirth among the primipara were evaluate with explore their experience, expactation and contributing factors which influence physical and psychological the primiparaous mothers who get EmCS. Results : Seven qualitative and four quantitative studies were found. This systemtic shows same experiences primiparous mother EmCS in qualitative studies, the dominant feeling is ”fear”. The other expereinces are pain in high intensity, have negative expereince, losing the child, lose of control, disappointed, feelings of failure and alienation for their infant, and difficulties to breastfeed esspecialy in holding and childcare the baby when already at home.The results from qualitative studies are supported by quantitative studies showed mothers with EmCS significant fear of delivery and have a more negative experience of childbirth (P< 0.001) and 80% more higher negative experience. Care before, during and after should be guided by foundation that mothers are the central of chilbirth actions, that grant their have autonomy and empowerment in this situation. Conclusion: This systematic review identified the primiparous mothers’ experience EmCS.“Fear” is the dominant felling for mothers’ EmCS, mothers needed social support and caring very approprietly in this situation esspecially in maternity ward. Caring for mothers as nurses being fully present in this moment,  avoid lack of the communication and give a control to get comfortable and feeling treated with respect and as an individual, mothers’ experience more positively.The suggest for this study is to development instrument include before, during and after delivery with caring, control and communication both for mothers and nurses.